2016
DOI: 10.1039/c6nr02004f
|View full text |Cite
|
Sign up to set email alerts
|

Electro-mechanical sensing in freestanding monolayered gold nanoparticle membranes

Abstract: The electro-mechanical sensing properties of freestanding monolayered membranes of dodecanethiol coated 7 nm gold nanoparticles (NPs) are investigated using AFM force spectroscopy and conductive AFM simultaneously. The electrical resistance of the NP membranes increases sensitively with the point-load force applied in the center of the membranes using an AFM tip. Numerical simulations of electronic conduction in a hexagonally close-packed two-dimensional (2D) array of NPs under point load-deformation are carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…[34] Gauvin et al characterized the electromechanical properties of freestanding GNP-monolayers using conductive AFM nanoindentation experiments. [35] In this paper, we report the fabrication of highly responsive resistive pressure sensors based on free-standing 1,9-nonanedithiol (9DT) cross-linked GNP membranes deposited onto silicon substrates with slit-shaped apertures. We demonstrate that the sensitivity of these pressure sensors can be tuned by reinforcement of the GNP membrane by an additional polymethylmethacrylate (PMMA) layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Gauvin et al characterized the electromechanical properties of freestanding GNP-monolayers using conductive AFM nanoindentation experiments. [35] In this paper, we report the fabrication of highly responsive resistive pressure sensors based on free-standing 1,9-nonanedithiol (9DT) cross-linked GNP membranes deposited onto silicon substrates with slit-shaped apertures. We demonstrate that the sensitivity of these pressure sensors can be tuned by reinforcement of the GNP membrane by an additional polymethylmethacrylate (PMMA) layer.…”
Section: Introductionmentioning
confidence: 99%
“…The as-deposited GNP films had a thickness between 41 nm and 68 nm. GNP multilayer composites commonly show ohmic conduction [14,33,35,40,41] and their conductivity can be described following a thermally activated tunneling model. [42][43][44] The GNP films used for sensor fabrication showed ohmic conductivities between 1 and 3 Ω −1 m −1 , which is roughly one order of magnitude higher than values observed earlier for 9DT cross-linked GNP films consisting of significantly smaller particles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the thin films formed by cross-linked or ligand-stabilized NPs have been studied in experiments [9][10][11]. Important chemical and physical properties for applications, including mechanical stiffness and conductivity, were measured in experiments [11][12][13]. Moreover, these studies showed that these properties can be controlled by the chemical nature and length of ligand, and the size of the NPs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, mechanical actuation and electron transport could be studied at the same time in a high sensitive electro-mechanical system. [61] The free-standing assemblies could bridge over microscale trenches, enabling direct detection of electron transport behaviours and optical collective surface plasmons. [81] The photoactivity characterization of free-standing assemblies from carboxylate ligand-coated zinc oxide nanocrystallites/InP/ZnS quantum dots demonstrated well-maintained quantum confining effects of the original nanocrystallites.…”
Section: Introductionmentioning
confidence: 99%